Science and Orthodox Christianity: Perceptions of Their Relationship in Greek Christian Journals (1980–2010) - Sakorrafou, Sandy (The journal of religion, 2020)
The article offers information on the International Scientific Conference hosted by the Holy Synod of the Church of Greece in collaboration with the National Centre for Scientific Research "Demokritos". Topics include examines that purpose of the conference was to present significant scientific and technological achievements and to discuss their relation to the Orthodox Christian faith.